Gambaran tingkat kecemasan dalam menghadapi UTBK SBMPTN pada calon mahasiswa baru angkatan 2020/2021 di Denpasar - Dhanira Mahaliana Bramantya Suanda Putri; Luh Made Indah Sri Handari Adiputra; Ketut Tirtayasa; Indira Vidiari Juhanna (DiscoverSys Inc., 2022)
Introduction: Such tight competition is suspected to cause anxiety in prospective new students in facing the computer-based written examination of the joint selection to enter state universities (UTBK SBMPTN). Anxiety is a combination of various responses that include intense networking, feeling worried and disturbing. Preparation for exams can create a high level of anxiety. However, anxiety can also be a positive energy when it is still at a low level. So, it is important when knowing the level of anxiety in prospective students facing the UTBK SBMPTN Methods: This study is a descriptive study with a retrospective approach. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS) questionnaire which was distributed to prospective students graduating from SMAN 4 Denpasar and SMA PGRI 2 Denpasar in 2021 who registered for the UTBK SBMPTN with a sample of 88 people. Results: The level of anxiety of respondents in this study had a relatively mild level of anxiety, namely 35 people (28%), 25 people (28%) experienced moderate anxiety and only 2 people (2%) experienced severe anxiety. Symptoms experienced by many respondents were difficulty concentrating (55 people), easily distracted (72 people), lethargic (60 people), restless (65 people). Conclusion: The level of anxiety of most of the respondents in this study had a relatively mild level of anxiety, namely as many as 35 people (40%). Pendahuluan: Persaingan yang begitu ketat diduga menimbulkan rasa cemas pada calon mahasiswa baru dalam menghadapi ujian tulis berbasis komputer seleksi bersama masuk perguruan tinggi negeri (UTBK SBMPTN). Kecemasan merupakan kombinasi dari berbagai respon mencakup ketakutan yang intens, merasa khawatir dan bersifat mengganggu. Persiapan untuk ujian dapat menciptakan tingkat kecemasan yang tinggi. Namun, kecemasan juga bisa menjadi energi positif ketika masih pada tingkatan rendah. Maka, penting mengetahui tingkatan kecemasan pada calon mahasiswa ketika menghadapi UTBK SBMPTN Hasil: Tingkat kecemasan responden dalam penelitian ini memiliki tingkat kecemasan yang tergolong ringan yaitu sebanyak 35 orang (40%), 25 orang (28%) mengalami cemas sedang dan hanya 2 orang (2%) yang mengalami cemas berat. Gejala yang banyak dialami oleh responden adalah sulit konsentrasi (55 orang), mudah terganggu (72 orang), lesu (60 orang), gelisah (65 orang). Simpulan: Tingkat kecemasan sebagian besar responden dalam penelitain ini memiliki tingkat kecemasan yang tergolong ringan yaitu sebanyak 35 orang (40%).